The Effects of Knowledge, Training, and Competency on the Performance: A Case of Local Public Agricultural Mentors - Erni Saptiowati S. (Britain International for Academic Research (BIAR) Publisher, 2021)
This research aimed to analyze the effects of knowledge, training, and competency on the performance, which local public agricultural mentors/officers in the Yapen Islands Regency are the unit analysis. Of 100 respondents were used as the saturated sample in this research. The research applied a survey method and used a five-point Likert scale as the instrument and the statistics program SPSS to analyze data. The analysis methods included descriptive analysis, validity and reliability tests, classical assumption test, and regression analysis. The research results show that the variables knowledge, training, and competency had significant positive effects on local public agricultural mentors' performance at the Yapen Islands Regency.